2011
DOI: 10.1007/s11596-011-0675-x
|View full text |Cite
|
Sign up to set email alerts
|

EGFR inhibitor enhances cisplatin sensitivity of human glioma cells

Abstract: Epidermal growth factor receptor (EGFR) is found to express at high levels in a variety of solid tumors including gliomas. This study was to examine the effect of an EGFR-tyrosine kinase inhibitor (AG1478) alone or in combination with cisplatin (CDDP) on the growth of glioma cells (U87). U87 glioma cells were treated with AG1478 (10 μmol/L) or CDDP (25 μmol/L) as a single agent or in combination for 24 or 48 h. The expression of EGFR and the components in its downstream signaling pathway [extracellular signal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Previous findings have confirmed that EGFR and its signaling pathways played an important role in the chemoresistance of cancer cells against CDDP-induced cell apoptosis (21,22). CDDP-resistant cancer cells have altered response to the EGF ligand and enhanced the activation of EGFR (23).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Previous findings have confirmed that EGFR and its signaling pathways played an important role in the chemoresistance of cancer cells against CDDP-induced cell apoptosis (21,22). CDDP-resistant cancer cells have altered response to the EGF ligand and enhanced the activation of EGFR (23).…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, we found that after exposure to CDDP, pEGFR expression was significantly increased, suggesting a potential mechanism through which T24 cells demonstrate chemoresistance to CDDP. According to the findings of Zhang et al (21), EGFR-tyrosine kinase inhibitor (AG1478) increased the apoptosis of the human U87 glioma cell line induced by CDDP. Thus, inhibition of the EGFR signaling pathway and reduction of the pEGFR expression may enhance the chemosensitivity of bladder cancer cells to CDDP.…”
Section: Discussionmentioning
confidence: 99%
“…However, its roles and regulatory mechanisms have not yet been fully elucidated. EGFR signaling plays an important role in drug resistance for the treatment of glioblastoma (52) and EGFR inhibitor can enhance cisplatin sensitivity of human glioma cells (52). We demonstrated herein that YY1 expression was increased in cisplatin-resistant U87MG cells and that the silencing of YY1 sensitized the U87MG-cR cells to cisplatin.…”
Section: Discussionmentioning
confidence: 64%
“…3). Other hub genes, such as EGFR (40), PDGFRA (32), FADD (41) and MET (42) are also associated with cancer. Cancer-related biomarkers are definitely a group or a series of factors.…”
Section: Discussionmentioning
confidence: 99%